Circulating Antibodies Against DSG1 and DSG3 in Patients with Oral Lichen Planus: A Scoping Review - Domenico De Falco; Francesca Iaquinta; Doriana Pedone; Alberta Lucchese; Dario Di Stasio; Massimo Petruzzi (Antibodies, 2025)
Oral Lichen Planus (OLP) is a chronic autoimmune disease with potential overlap with Pemphigus Vulgaris (PV), particularly in erosive forms. Desmoglein 1 and 3 are transmembrane glycoproteins of desmosomes, typically involved in PV. This scoping review aims to evaluate the presence and potential pathogenetic role of anti-desmoglein 1 (Dsg1) and anti-desmoglein 3 (Dsg3) antibodies in OLP. A literature search was conducted on MEDLINE/PubMed, Ovid, and Scopus up to April 2025. Human studies reporting OLP patients with anti-Dsg1 and/or anti-Dsg3 antibodies were included. Data from 11 studies were analyzed by diagnosis, age/sex, oral site involvement, immunofluorescence, and ELISA testing. Erosive OLP was most frequently associated with anti-Dsg1/Dsg3 positivity, mainly in women aged 40–60. Immunofluorescence was positive in some cases, while the ELISA test almost consistently detected anti-Dsg1 and Dsg3 antibodies. However, in many instances, antibody titers did not reach the threshold value, despite the presence being detectable. This finding suggests that anti-Dsg1/Dsg3 antibodies may represent epiphenomena of chronic inflammation in erosive OLP, indicating an immune-serological overlap with PV but lacking direct pathogenicity. Furthermore, the role of Dsg3 in oral squamous cell carcinoma, by promoting enzymes that degrade the extracellular matrix and enhance tumor invasiveness, highlights the complex functions of desmogleins beyond autoimmunity.